Information Behavior and Access to Online Live Streaming: A Pilot Study of Avid Viewers in the Philippines - Yap, Joseph Marmol; Agulto, Ernani Agulto (Ukrainian State University of Science and Technologies, Dnipro, 2025)
ENG: Objective. As social media progresses in the Philippines, access to entertainment and online content has become convenient for today’s digital users. Given that consumption often involves purchasing services, and online user behavior is influenced by freely available content, this study investigates how avid beauty pageant fans search for live online content. The study asks the question: how do Filipino beauty pageant fans consume online live streaming content amidst the evolving landscape of social media and digital access? Methods. This pilot study explored the previously unexamined information-seeking behaviors of individuals looking for free items when they engage with online beauty pageant content. Using a semi-structured online interview, responses were organized according to demographics and interview questions. Convenience sampling was used to gather initial data for this pilot study and improve the study design. Results. A diverse group of 14 participants took part in the online survey, with age ranging from 26 to 52 years old, belonging to different professions. 93% avid fans of beauty pageants can identify local and international pageants. Participants were able to search the information they need by searching for the official website or social media pages and by reading the comments section of social media pages for tips and links. Participants were willing to share free access with others. However, most of the participants were not willing to pay for this kind of entertainment. Since libraries have the unique ability to expand their media services and collections based on their specific missions and target audiences, libraries have to address the needs of their enthusiastic online entertainment seekers. As the data provided, 66.67% strongly agree that access to digital entertainment content should be part of the services offered by public libraries to engage users and that the same number of participants strongly agree that streaming media should be a constant service of public libraries. Conclusions. This study explored the previously unexamined information seeking behavior of individuals seeking free items when engaging with online beauty pageant content. As a call to action, libraries, as sources of media and content, may provide video streaming services to diverse users, provided they are aligned with their mission and objectives.

UKR: Мета. З розвитком соціальних медіа на Філіппінах доступ до розваг та онлайн-контенту став зручним для сучасних користувачів цифрових технологій. З огляду на те, що споживання часто передбачає придбання послуг, а поведінка онлайн-користувачів залежить від вільно доступного контенту, це дослідження вивчає, як шанувальники конкурсів краси шукають онлайн-контент у прямому ефірі. Дослідження ставить питання: як філіппінські шанувальники конкурсів краси споживають онлайн-контент у прямому ефірі в умовах розвитку соціальних медіа та цифрового доступу? Методика. Це пілотне дослідження вивчало раніше не досліджену поведінку осіб, які шукають безкоштовні матеріали, коли вони взаємодіють з онлайн-контентом конкурсів краси. За допомогою частково структурованого онлайн-інтерв'ю відповіді були організовані відповідно до демографічних даних та питань інтерв'ю. Для збору початкових даних для цього пілотного дослідження та вдосконалення методу дослідження було використано випадкову вибірку. Результати. В онлайн-опитуванні взяла участь різноманітна група з 14 учасників віком від 26 до 52 років, які представляли різні професії. 93 % шанувальників конкурсів краси можуть ідентифікувати місцеві та міжнародні конкурси. Учасники могли знайти потрібну інформацію, шукаючи офіційний вебсайт або сторінки в соціальних мережах, а також читаючи коментарі на сторінках соціальних мереж, де містилися поради та посилання. Учасники були готові поділитися безкоштовним доступом з іншими. Однак більшість учасників не були готові платити за такий вид розваг. Оскільки бібліотеки мають унікальну можливість розширювати свої медіапослуги та колекції на основі своїх конкретних місій та цільової аудиторії, бібліотеки повинні задовольняти потреби своїх ентузіастів, які шукають розваг в Інтернеті. Згідно з наданими даними, 66,67 % повністю погоджуються, що доступ до цифрового розважального контенту повинен бути частиною послуг, що надаються публічними бібліотеками для залучення користувачів, і така ж кількість учасників повністю погоджується, що потокове медіа має бути постійною послугою публічних бібліотек. Висновки. Це дослідження вивчало раніше не досліджену поведінку осіб, які шукають безкоштовні матеріали, коли взаємодіють з онлайн-контентом про конкурси краси. Як заклик до дії, бібліотеки, як джерела медіа та контенту, можуть надавати послуги потокового відео різноманітним користувачам, за умови, що це відповідає їхній місії та цілям.
Інформаційна поведінка та доступ до онлайн-трансляцій: пілотне дослідження серед активних користувачів на Філіппінах
J. Yap: ORCID 0000-0002-7852-1047; E. Agulto: ORCID 0009-0009-5385-5161
Keywords: freebie seekers; information seeking; information behavior; beauty pageants; live streaming; online content; користувачі безкоштовних послуг; пошук інформації; інформаційна поведінка; конкурси краси; прямі трансляції; онлайн-контент; SOCIAL SCIENCES; SOCIAL SCIENCES::Other social sciences